CAMPUR KODE PADA PIDATO PRESIDEN SBY DALAM PERAYAAN HUT KE-69 REPUBLIK INDONESIA - Unpris Yastanti (Center of Language and Cultural Studies, 2016)
This study aims to identify code mixing used by the late President Susilo Bambang Yudhoyono (SBY) in his speech delivered in the 69th Indonesian Indepence Day. This study used content analysis implementing qualitative approach. A text of the official speech issued by the presidential office was used as sources of data. Corpora in the text was identified and classified as they were presented as code mixing in the social interaction contexts. This study revealed (1) 11 code mixings were present in the president speech, (2) types of code mixing in the speaach were insertion, and (3) the code mixing styles appearing in the presidential speech were communicatively delivered.